Effects of Linpan nature therapy on health benefits in older women with and without hypertension - Ye, Xiang; Dou, Zhiwen; Jiang, Mingyan; Luo, Zhenghua; Li, Mao; Tang, Haixiong; Huang, Xiao; Wang, Yuqian; Dong, Liwei; Mao, Xiaoguang; Feng, Yu (Frontiers in Public Health, 2023)
(1) Background: Nature therapy can significantly benefit the physiology and psychology of middle-aged and older people, but previous studies have focused on forest environments. The restoration potential of rural environments in urban fringe areas, which are more accessible to older people on a daily basis, has not been fully studied. This study assessed the effects of nature therapy on the physical and mental health of older women in a rural setting (locally known as Linpan) in the urban fringe area of Chengdu, China. (2) Methods: We recruited a total of 60 older women (65.3±5.5 years old) living in cities for 3 days of nature therapy in the winter (30 subjects) and spring (30 subjects), including 20 hypertensive patients. (3) Results: The results showed that the overall blood pressure, pulse and sleep dysfunction rating scores of the participants were significantly lower than the pretest levels, and the finger blood oxygen saturation, mid-day salivary alpha-amylase and cortisol were increased post-treatment. Increases in these biomarker indicates and increase in stress. There were significant differences in the changes in systolic blood pressure between the hypertension group (HTN) and the normal group (normal) (HTN decreased by 8.8%, normal decreased by 5.4%), salivary alpha-amylase content (HTN decreased by 0.3%, normal increased by 16.9%) and sleep dysfunction rating scores (HTN decreased by 59.6%, normal decreased by 54%). The decreases in systolic blood pressure and pulse in the winter group were higher than those in the spring group by 1.8% and 4.4%, respectively, while the increases in salivary alpha-amylase content and salivary cortisol content were lower than those in the spring group by 11.7% and 11.2%, respectively, and the decrease in sleep dysfunction rating scores was lower than that in the spring group by 7.1%. (4) Conclusions: Our study concluded that nature therapy based on various health activities in the Linpan has significant health effects on older women. It can regulate blood pressure and pulse in older women, relieve cardiovascular disease, improve sleep quality. Meanwhile, older women with high blood pressure experienced a more significant effect than the healthy group.